2022
DOI: 10.48550/arxiv.2208.07231
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metasurface-Based Realization of Photonic Time Crystals

Abstract: Photonic time crystals are artificial materials whose electromagnetic properties are uniform in space but periodically vary in time. The synthesis of such materials and experimental observation of their physics remain very challenging. In this work, we extend the concept of photonic time crystals to metasurfaces. We demonstrate that time-varying metasurfaces preserve key physical properties of volumetric time crystals, in particular, generating momentum bandgaps for surface and free-space waves. Moreover, in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Longer wavelengths relax the constraints of the ultrashort cycle time. It is, therefore, no surprise that the first observation of the momentum gap in a time-modulated medium was done at radio frequencies [27] and the first PTCdominated effects such as the exponential growth of EM waves in a temporally varying metasurface, have been demonstrated in the microwave regime [28]. These experiments are also promising signs that for proof-of-concept devices, plasmas or RF circuits can be viable media [29].…”
Section: Ultrafast Index Changementioning
confidence: 89%
“…Longer wavelengths relax the constraints of the ultrashort cycle time. It is, therefore, no surprise that the first observation of the momentum gap in a time-modulated medium was done at radio frequencies [27] and the first PTCdominated effects such as the exponential growth of EM waves in a temporally varying metasurface, have been demonstrated in the microwave regime [28]. These experiments are also promising signs that for proof-of-concept devices, plasmas or RF circuits can be viable media [29].…”
Section: Ultrafast Index Changementioning
confidence: 89%
“…31-33 and the recent experimental results in Refs. [34][35][36]; the additional anisotropic character could be implemented via a suitable (asymmetric) design of the reconfigurable meta-atoms, and should not pose insurmountable obstacles.…”
Section: Discussionmentioning
confidence: 99%
“…[31,32]. While there are inherent constraints and technological challenges in the temporal modulation of constitutive parameters [33], experimental studies are continuing to progress, and recent results have demonstrated feasibility in this area [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, frequency and momentum switch their roles making possible such effects as the frequency conversion under time modulation of materials [24]. In the temporal analogs of photonic crystals, one can observe the momentum bandgaps inside which one can observe amplification of waves [25][26][27][28]. However, practical possibilities of time-varying photonics are strongly limited by the difficulties with fast and spatially uniform modulations of materials and by interference with common nonlinear effects [29].…”
Section: Introductionmentioning
confidence: 99%